Perancangan Kampung Tematik River Tubing Mayangsari Menjadi Destinasi Wisata Kota Semarang - Grandy Loranessa Wungo; Anis Meilitasari Sugiyarto; Natania Nysa Pertiwi (Jurnal Riptek, 2023)
Thematic villages have a big role in reducing the poverty rate in Semarang City. The existence of tourism-oriented development will encourage thematic villages to have more impact on the people's economy. The River Tubing Mayangsari thematic village has the potential to be developed, therefore there is a need for planning and design recommendations for tourist destinations. The method used is a quantitative and qualitative descriptive analysis approach in data analysis and data collection techniques using field techniques and literature/document studies. The results obtained in this service are recommendations for socio-economic planning and infrastructure design for the Mayangsari River Tubing. This community service is expected to become a consideration and recommendation for the Regional Development Planning Agency for the City of Semarang in bringing the Mayangsari River Tubing Thematic Village to a Tourist Destination in the City of Semarang.